National Income Estimates in the Statistical Policy of an Underdeveloped Area: A Comment - Hollinger, William C. (Review of Economic Studies, 1954)
Journal Article National Income Estimates in the Statistical Policy of an Underdeveloped Area: A Comment Get access William C. Hollinger William C. Hollinger Diakarta, Indonesia Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 3, 1954, Pages 220–225, https://doi.org/10.2307/2295879 Published: 01 January 1954